Influence of pressure on the oxidation resistance of carbon fiber reinforced ZrB2/SiC composites at 2000 and 2200 °C. (15th May 2021) - Vinci, Antonio; Reimer, Thomas; Zoli, Luca; Sciti, Diletta
Highlights: C-ZrB2 /SiC composites were oxidized up to 2200 °C at different pressure in a controlled environment. Up to 1650 °C, the increase of SiC is beneficial due to the formation of a protective silica layer. Above 2000 °C, the trend is inverted and the SiC increase is detrimental due to rapid removal. At low pressure the degree of oxidation is much lower in spite of SiC active oxidation. Abstract: The influence of pressure on the oxidation resistance of C-ZrB2 /SiC composites was studied. Materials were tested in air at 2000−2200 °C at 1−900 mbar. SEM analysis on the tested samples revealed the formation of an outer compact layer of ZrO2 and an intermediate layer of ZrO2 -SiO2 as well as a porous interface layer of ZrO2 . SiC increase was beneficial up to 1650 °C, then the trend was inverted. At 1 mbar all samples were visibly less damaged and displayed similar performance both at 2000 and 2200 °C, indicating that oxidation resistance is mostly dominated by fiber consumption, which is more severe at ambient pressure.